(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
This study examines the institutional changes that have influenced long-term structural shifts in the local economy, specifically focusing on tourism transformation. The article aims to assess the institutional changes in tourism destinations and explain how these changes impact sustainable tourism destination performance. Through Robert K. Yin-style case studies (2009), the study findings reveal that the Ledok Sambi Tourism Destination has experienced institutional changes that have altered the destination’s governance structure from convergent and collaborative to divergent and separate. Additionally, the shift in institutional character from inclusive to extractive institutions has led to tourism performance that is less conducive to sustainability. The relationship between institutional change and performance, this research also finds that institutions can trap destinations that worsen tourism performance, resembling a paradoxical trap box between sustainable tourism objectives. The study suggests the importance of orchestration and alignment of formal institutions, bureaucracy that serves and empowering the community to get out of the paradoxical box